2016
DOI: 10.1093/gerona/glw105
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Extends the Lifespan ofCaenorhabditis elegansvia Insulin/IGF-1 Signaling Pathway

Abstract: Coffee and tea, two of the most popular drinks around the world, share many in common from chemical components to beneficial effects on human health. One of their shared components, the polyphenols, most notably chlorogenic acid (CGA), was supposed to account for many of the beneficial effects on ameliorating diseases occurred accompanying people aging, such as the antioxidant effect and against diabetes and cardiovascular disease. CGA is also present in many traditional Chinese medicines. However, the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 75 publications
7
89
0
2
Order By: Relevance
“…1: Gallic acid, 2: protocatechuic acid, 3: catechin, 4: p-hydroxy benzoic acid, 5: chlorogenic acid, 6: caffeic acid, 7: epicatechin, 8: syringic acid, 9: vanillin, 10: p-coumaric acid, 11: ferulic acid, 12: sinapinic acid, 13: benzoic acid, 14: o-coumaric acid, 15: rutin, 16: hesperidin, 17: rosmarinic acid, 18: eriodictyol, 19: cinnamic acid, 20: quercetin, 21: luteolin, 22: kaempferol, 23: apigenin. antihypertension, antiobesity, and neuroprotective effects. In concordance with our results, chlorogenic acid was recently found to extend the lifespan of C. elegans by up to 20.1%, delay the age-related decline of body movement, and improve stress resistance (Zheng et al, 2017). The authors performed subsequent genetic analysis with worm mutants and revealed that chlorogenic acid extends the lifespan of C. elegans mainly through DAF-16 in the insulin/IGF-1 signaling pathway.…”
Section: Discussionsupporting
confidence: 90%
“…1: Gallic acid, 2: protocatechuic acid, 3: catechin, 4: p-hydroxy benzoic acid, 5: chlorogenic acid, 6: caffeic acid, 7: epicatechin, 8: syringic acid, 9: vanillin, 10: p-coumaric acid, 11: ferulic acid, 12: sinapinic acid, 13: benzoic acid, 14: o-coumaric acid, 15: rutin, 16: hesperidin, 17: rosmarinic acid, 18: eriodictyol, 19: cinnamic acid, 20: quercetin, 21: luteolin, 22: kaempferol, 23: apigenin. antihypertension, antiobesity, and neuroprotective effects. In concordance with our results, chlorogenic acid was recently found to extend the lifespan of C. elegans by up to 20.1%, delay the age-related decline of body movement, and improve stress resistance (Zheng et al, 2017). The authors performed subsequent genetic analysis with worm mutants and revealed that chlorogenic acid extends the lifespan of C. elegans mainly through DAF-16 in the insulin/IGF-1 signaling pathway.…”
Section: Discussionsupporting
confidence: 90%
“…Reduction in insulin signaling is a beneficial way to increase lifespan (52)(53)(54), and complete and partial reduction of insulin release increases lifespan in flies (55). In our system, we had strong evidence that insulin signaling was reduced through at least 2 different, synergistically acting mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…All strains were cultured on fresh NGM plates for 2–3 generations without starvation, and lifespan analysis was conducted at 20°C, unless otherwise stated. Late L4 larvae or young adults were transferred to NGM plates containing inactivated OP50 (65°C for 30 min) and 20 μM FUdR to inhibit progeny growth [ 7 , 39 ]. The day that L4 larvae or young adults were transferred to an NGM plate was defined as test day 0.…”
Section: Methodsmentioning
confidence: 99%